Stock Investment Education through PKK to Build Indonesian Human Resources for Family Welfare - Hastutik, Sri; Yuliana, Rachma; Rokhmawati, Dian (Edumedia Solution, 2025)
The low level of financial literacy in Indonesia, with a rate of only 38.03%, is a challenge in managing family finances, especially among homemakers. Homemakers who are members of the Family Welfare Empowerment (PKK) have great potential to be empowered. Still, most do not yet understand stock investment as an alternative for long-term financial management. This program is designed to improve the financial literacy of PKK mothers through stock investment education to help them manage family finances more effectively and sustainably.The solution implemented involves community-based education with a participatory approach. The implementation method includes interactive training, stock investment simulations using a digital platform, and real-world practice assistance. This program is implemented for three months in three stages: basic education, simulation, and direct application.The results showed a significant increase in participant understanding, from 20% who understood the basic concept of stock investment before training to 85% after training. As many as 70% of participants started real investments with small funds. In addition, this program forms stock study groups, increases self-confidence, and creates an investment culture in the community. This program provides innovative solutions to empower local communities and improve family welfare through better financial literacy.